Medium/heavy duty truck test (Clifton Park, NY, 2007)
This fourth edition has been completely updated to provide the most current ASE test preparation material for Medium/Heavy Duty Trucks available anywhere. Test T5: Suspension and Steering provides valuable preparation for Medium/Heavy Duty Truck technicians seeking certification in the Suspension and Steering ASE Medium/Heavy Duty Truck Technician Certification area. Readers are afforded scores of opportunities to ascertain their knowledge of critical concepts, through the extensive array of sample problems, ASE-style exams, and competency-specific test questions required for certification by ASE. Refresher materials, helpful test-taking strategies, and thorough explanations round out this comprehensive preparation package.
Keywords: Trucks,Trucks,Automobile mechanics,Động cơ ô tô,Xe tải,Xe tải; Maintenance and repair,Examinations,Maintenance and repair,Certification,Chứng nhận,Bảo dưỡng và sửa chữa,Bảo dưỡng và sửa chữa,Kiểm tra